Squaring the circle: EFA in the post-2015 global agenda - Ahmed, Manzoor (© 2014 Elsevier Ltd., 2016)
This article was published in the International Journal of Educational Development [© 2014 Elsevier Ltd.] and the definite version is available at : http://doi.org/10.1016/j.ijedudev.2014.07.014. The Journal's website is at:http://www.sciencedirect.com/science/article/pii/S0738059314000790